LEARNING OBSTACLES YANG DIHADAPI SISWA DALAM MEMAHAMI TOPIK RELASI DAN FUNGSI - Lafita Rahmi; Kartika Yulianti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Function is one of the important basic concepts in mathematics, as well as a topic where students faced obstacles in learning it. This research was qualitative with a case study design with the aims to obtain a description of the learning obstacles faced by students in the topic of relations and functions. The research subject that involved 25 students of grade 8th of a junior high school in Padang Pariaman was given test dealing with relations and functions, 5 of which also participated in-depth interview, and a document study was carried out on the source books used by students. The data were analyzed using the stages of data collecting, reducing, and analyzing to get conclusion. The results showed that there are students’ learning obstacles, which include ontogenic obstacle, didactical obstacle, and epistemological obstacle. The results of this study can be used to design an instructional material for relations and functions to anticipate the learning obstacles that will be faced by students in the next learning.